ChemInform Abstract: Supramolecular Recognition Influences Magnetism in [X@HVIV8VV14O54] 6‐ Self‐Assemblies with Symmetry‐Breaking Guest Anions. Issue 17 (April 2015) - Monakhov, Kirill Yu.; Linnenberg, Oliver; Kozlowski, Piotr; van Leusen, Jan; Besson, Claire; Secker, Tim; Ellern, Arkady; Lopez, Xavier; Poblet, Josep M.; Koegerler, Paul
Abstract Crystals of (Et4N)6 [(VO2F2)HV22O54] are prepared by mixing Et4NBF and (H4N)8 [H9V19O50]·11H2O in the molar ratio of 8.7:0.39 in aqueous solution (80 °C, 72 h, 79% yield).